Pemisahan Campuran Naftalen-Difenil Dengan Metode Progressive Freezing - Perpustakaan UGM, i-lib ([Yogyakarta] : Unit Informasi Inovasi Proses Pembelajaran (UI2P2) Universitas Gadjah Mada, 2003)
" The objectives of this research are to validate a mathematical model to predict the impurities concentration in solid phase and to study the effect of agitation rate to the purity of solid product, represented by coefficient distribution of minor component. Naphthalene-diphenyl mixture with initial temperature at about 80-85 "C was cooled slowly enough until a solid phase was formed. Every 0.2 cm of solid phase was formed, the liquid sample was analyzed to evaluate the concentration of naphthalene. The agitation rates that were studied are 120, 150, 175, 200 and 250 rpm and temperature of cooling medium is 32"C. Naphthalene would be distributed in liquid and solid phase with the value of distribution coefficient between 0.1037 and 0.1153. Generally, the result of this research proved that higher purity product could be achieved at lower agitation rate. The relationship between distribution coefficient and the controlling variable can be expressed by the equation: 0.073 The average deviation of k model and k data is 1.82 %. The equation is valid for Reynolds number ranged from 240 up to 500. The effect of controlling variable is not significant to the coefficient distribution. It means that k is not mass transfer parameter but it is an equilibrium phase parameter.